2015
DOI: 10.1007/s40097-015-0180-z
|View full text |Cite
|
Sign up to set email alerts
|

Photobiological synthesis of noble metal nanoparticles using Hydrocotyle asiatica and application as catalyst for the photodegradation of cationic dyes

Abstract: Solar light induced photo catalysis by plasmonic nanoparticles such as Au and Ag is an important field in green chemistry. In this study an environmental benign method was investigated for the rapid synthesis of colloidal Ag and AuNPs using the extract of Hydrocotyle asiatica, as a reducing and stabilizing agent under sunlight irradiation. The nanoparticles were formed in few seconds and were characterized by UV-Vis., FT-IR, TEM, EDAX, XRD, DLS and Zetasizer. The nanoparticles were stable in aqueous solution f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 64 publications
1
19
0
1
Order By: Relevance
“…It was found that the adsorption rate is rapid at the initial stages (Figure 8) because of the high vacant site to adsorb heavy metal and the system reaches equilibrium after 120 min and 150 min respectively. After equilibrium time, removal process became slow because of pore diffusion or saturation of adsorbent with heavy metals [5][6][7]. The degree of removal was very high for heavy metal by using AgNPs, more than 80% of Cd and Pd removal was achieved in 120 and 150 min respectively and after equilibrium time, the removal rate became slow [9].…”
Section: Catalytic Propertymentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the adsorption rate is rapid at the initial stages (Figure 8) because of the high vacant site to adsorb heavy metal and the system reaches equilibrium after 120 min and 150 min respectively. After equilibrium time, removal process became slow because of pore diffusion or saturation of adsorbent with heavy metals [5][6][7]. The degree of removal was very high for heavy metal by using AgNPs, more than 80% of Cd and Pd removal was achieved in 120 and 150 min respectively and after equilibrium time, the removal rate became slow [9].…”
Section: Catalytic Propertymentioning
confidence: 99%
“…Recently, a simple and eco-friendly green approach for synthesis of silver nanoparticles by various plant extracts have drawn the attention of academician and researcher because of its advantage over physical and chemical methods [4][5][6][7][8][9][10][11][12]. Synthesis of nanoparticles by green approach is emerging field because of its various advantages over the other process like nontoxic, ecofriendly and low cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different fungi like Fusarium oxysporum [10], Cladosporium cladosporioides [11], Fusarium semitactum [12], plants like Syzygium aromaticum [13], Medicago sativa [14], Azadirachta indica [15], Terminalia cuneata [16], and Trignellafoenum graecum seeds [17] have been employed to synthesize metal nanoparticles. Recently, sunlight-induced rapid synthesis of silver nanoparticles has been reported by our group [18,19]. Biosynthesis of silver nanoparticles using bark of Cinnamon zeylanicum [20], Piper nigrum [21], Breynia rhamnoides [22], Avicennia marina [23], Callicarpa maingayi [24], Cissus quadrangularis [25], Artocarpus elasticus [26], and Saraca indica [27] has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is worthy to note that the calculated rate constant is much higher than those previously reported values for the degradation of MB by using semiconductor photocatalysts, [66][67][68] moreover, the rate constant for the Fe 3 O 4 -Ag seeds nanocrystals is signicantly higher than the previous works by utilizing noble metal catalysts. [69][70][71] It can been noticed that the time required to catalytic reduce decreases with the increase of the amount of silver seeds deposited on the Fe 3 O 4 surfaces. It is generally accepted that the catalytic reaction of silver nanocrystals occurs through electron transfer.…”
Section: Catalytic Studies Of Fe 3 O 4 -Ag Seeds Nanocrystalsmentioning
confidence: 99%